Wild Wild West : une série au carrefour des affirmations dans les États-Unis du milieu des années 1960 - Jean Ruhlman (Transatlantica)
The Television series The Wild Wild West (WWW) was broadcast on CBS from 1965 to 1969 and it was an immediate success. While it cleverly brings together the aesthetics of the western and spy fiction, its success also has to do with the historical and social relevance of the themes it addresses. The series questions diverse constitutive elements of the mythology of the West, as it undermines the supposed virtues of the pioneering local communities as well as those asserted by the conquest of the West in its final stage after the Civil War. In a more or less coded and allusive way, the politics of the series are mainly geared towards political, diplomatic, and economic progress. The series also takes sides against several forms of conservatism, brings a subtle support to the moral emancipation and empowerment of the African American and gay minorities who had achieved differing stages of mobilization in the 1960s. For all these reasons, The Wild Wild West remains as a nonconventional series, with an altogether coherent message, heralding the major protest movements of the following years.